1985
DOI: 10.1037/0022-3514.49.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Personal involvement and strategies for making contingency judgments: A stake in the dating game makes a difference.

Abstract: To examine the relation between degree of involvement in a task and the complexity of strategy a subject applies to the task, we randomly assigned 48 female university volunteers to either a dating condition (high-involvement) or one of two (low-involvement) control conditions. These subjects performed a covariation judgment task for which the likelihood of their using simple or complex strategies was calculated. High-involvement subjects used more complex strategies and tended to be more accurate. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 26 publications
3
67
0
Order By: Relevance
“…For example, satisfying defense motivation may require monitoring the direction and quality of the information in relation to a prior attitude, belief, or behavior. In contrast, satisfying accuracy motivation may require monitoring the direction and quality of the information as well as attending to and correcting for any systematic biases in exposure (e.g., Harkness, DeBono, & Borgida, 1985; McAllister, Mitchell, & Beach, 1979; Tetlock, 1983; Tetlock & Kim, 1987). Given these possibilities, future research might explore the automatic and controlled processes that influence information selection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, satisfying defense motivation may require monitoring the direction and quality of the information in relation to a prior attitude, belief, or behavior. In contrast, satisfying accuracy motivation may require monitoring the direction and quality of the information as well as attending to and correcting for any systematic biases in exposure (e.g., Harkness, DeBono, & Borgida, 1985; McAllister, Mitchell, & Beach, 1979; Tetlock, 1983; Tetlock & Kim, 1987). Given these possibilities, future research might explore the automatic and controlled processes that influence information selection.…”
Section: Discussionmentioning
confidence: 99%
“…there is unlikely to be much energy devoted to intensive testing. And, indeed, in such cases, subjects do appear to rely upon quick and dirty heuristic strategies~Harkness, DeBono, and Borgida, 1985!. What is central to pragmatic hypothesis testing accounts is another sort of cost to the settling of such questions: The cost of anticipated errors. Motivation for hypothesis testing is provided by a subject's regard for the costs of being mistaken.…”
Section: The Rationale Of Motivated Believingmentioning
confidence: 99%
“…First, they suggested that people might not debias because they tend not to accept that their perspective is biased; this effect is called the “bias blind spot” or the “not me” bias [49], [50], [51]. Second, they alerted that interventions are more effective when people perceive that the bias to be corrected is relevant to their daily lives [47], [52]. Following Lilienfeld et al's [10] recommendations, we expected that we might improve the effectiveness of our debiasing intervention by first demonstrating to the participants how easily they might arrive at biased conclusions and how relevant these conclusions might be to their daily lives.…”
Section: Introductionmentioning
confidence: 99%